Determinants of early working impairments in multiple sclerosis - Moccia, Marcello; Fontana, Luca; Palladino, Raffaele; Falco, Fabrizia; Finiello, Ferdinando; Fedele, Mauro; Lanzillo, Roberta; Reppuccia, Liberata; Triassi, Maria; Brescia Morra, Vincenzo; Iavicoli, Ivo (Frontiers in Neurology, 2022)
Introduction Unemployment can directly affect social status and identity. Assessing and adjusting determinants of early working impairments in a chronic disease can thus reduce its long-term burden. Hereby, we aim to evaluate differences in occupational history and early working impairments between people with multiple sclerosis (MS) and healthy workers. Methods This is a cross-sectional study comparing 71 workers with MS [age 41.7 ± 9.4 years; females 59.1%; EDSS 2.0 (1.0–6.0)] and 71 controls (age 42.6 ± 11.9 years; females 33.8%). All participants filled in Work Ability Index (WAI), Work Productivity and Activity Impairment (WPAI), European Questionnaire for Quality of Life (EuroQoL), Beck Depression Inventory II (BDI-II), and Pittsburgh Sleep Quality Index (PSQI). In MS, we further collected expanded disability status scale (EDSS), MS Questionnaire for Job difficulties (MSQ-Job), Fatigue severity scale (FSS), and the Brief International Cognitive Assessment for MS (BICAMS). Results Workers with MS were more working disabled (p < 0.01), less exposed to workplace risks (p < 0.01), and more limited in fitness to work (p = 0.01), compared with controls. On linear regression models adjusted by age, sex, education, and type of contract, people with MS had worse WAI (Coeff=−5.47; 95% CI = −7.41, −3.53; p < 0.01), EuroQoL (Coeff = −4.24; 95% CI = −17.85, −6.50; p < 0.01), BDI-II (Coeff = 3.99; 95% CI = 2.37, 7.01; p < 0.01), and PSQI (Coeff = 4.74; 95% CI = 3.13, 7.61; p < 0.01), compared with controls, but no differences in WPAI (p = 0.60). EuroQoL, BDI-II, and PSQI were equally associated with both WAI and WPAI in MS and controls (all p< 0.01). In MS, worse MSQJob was associated with higher EDSS (Coeff = 5.22; 95% CI = 2.24, 7.95; p < 0.01), progressive disease (Coeff = 14.62; 95% CI = 5.56, 23.69; p < 0.01), EuroQoL (Coeff = 4.63; 95% CI = 2.92, 6.35; p < 0.01), FSS (Coeff = 0.55; 95% CI = 0.38, 0.72; p < 0.01), and cognitive impairment (Coeff = 4.42; 95% CI = 0.67, 8.22; p = 0.02). Discussion Early factors associated with working difficulties in MS include disability, fatigue, depression, and cognitive dysfunction. Early identification of clinical features potentially causing working difficulties should be considered to enhance job retention, along with targeted prevention and protection measures.